2019
DOI: 10.1097/mcg.0000000000000990
|View full text |Cite
|
Sign up to set email alerts
|

Modification Patterns of Urinary Albumin Correlates With Serum Albumin and Outcome in Severe Alcoholic Hepatitis

Abstract: u-Alb modifications are reflective of serum albumin modifications. Further baseline u-Alb levels could be exploited to predict steroid response and mortality in SAH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Alternatively, high circulating levels of bacterial DNA may predict the development of infection within the first 7 days of corticosteroid therapy and identify non‐responders . A further study found that circulating microvesicles, reflective of oxidative stress, are more numerous and larger in patients with a Lille non‐response as are higher levels of urinary albumin . Higher levels of lipopolysaccharide, procalcitonin and the presence of the systemic inflammatory response syndrome (SIRS) have also been shown to indicate a worse outcome at 90 days in corticosteroid treated patients .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Alternatively, high circulating levels of bacterial DNA may predict the development of infection within the first 7 days of corticosteroid therapy and identify non‐responders . A further study found that circulating microvesicles, reflective of oxidative stress, are more numerous and larger in patients with a Lille non‐response as are higher levels of urinary albumin . Higher levels of lipopolysaccharide, procalcitonin and the presence of the systemic inflammatory response syndrome (SIRS) have also been shown to indicate a worse outcome at 90 days in corticosteroid treated patients .…”
Section: Discussionmentioning
confidence: 97%
“…as are higher levels of urinary albumin. 19 Higher levels of lipopolysaccharide, procalcitonin and the presence of the systemic inflammatory response syndrome (SIRS) have also been shown to indicate a worse outcome at 90 days in corticosteroid treated patients. 20 Unfortunately it was not possible to calculate the SIRS for our patients as the respiratory component was not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is involved in the development of alcoholic liver disease as a trigger for cellular immune responses . In 2018, Das et al conducted a cross‐sectional study of 100 biopsy‐proven severe alcoholic hepatitis patients. Their results revealed that, compared to stable compensated alcoholic liver cirrhosis patients or healthy controls, the AOPPs in severe alcoholic hepatitis patients were significantly higher, both in the urine and serum.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Studies included in the systematic review reported data on 1844 participants (909 with NAFLD, 169 with ALD and 766 healthy controls). Three studies focused on ALD [37][38][39] and eight studies on NAFLD [29][30][31][32][33][34][35][36]. In studies on ALD, the diagnosis was confirmed with a biopsy.…”
Section: Systematic Reviewmentioning
confidence: 99%